Effects of Support, Particle Size, and Process Parameters on Co3O4 Catalyzed H2O Oxidation Mediated by the [Ru(bpy)3]2+ Persulfate System - Yang, C.C.; Eggenhuisen, T.M.; Wolters, M.; Agiral, A.; Frei, H.; de Jongh, P.E.; de Jong, K.P.; Mul, G. (Wiley, 2013)
Water oxidation over highly dispersed cobalt oxide particles in porous silica was studied, applying photo-activation of the Ru(bpy)32+ photosensitizer complex and the sacrificial electron acceptor (S2O82−). Under identical process conditions, 4 nm crystalline Co3O4 particles dispersed in SBA-15, obtained by calcination of impregnated Co(NO3)2 in an NO/N2 atmosphere, showed higher O2 evolution rates than 7 nm Co3O4 particles, obtained by air calcination of the same catalyst precursor. A similar trend was observed for Co3O4 dispersed in MCM-41, although MCM-41 catalysts showed lower O2 production rates than SBA-15 catalysts of comparable Co3O4 sizes. The positive effect of a small Co3O4-particle size is related to the higher amount of surface sites of Co3O4 interacting with the Ru complex, which subsequently leads to water oxidation. The effect of the silica scaffold was demonstrated to be the result of the higher surface area of MCM-41 versus SBA-15 (≈1000 m2 g−1 versus 600 m2 g−1). Consequently a larger fraction of the [Ru(bpy)3]2+ photosensitizer complex immobilizes on the silica walls, and thus becomes ineffective to stimulate water oxidation. The nanosized Co3O4 particles in general were more effective than previously reported micron-sized crystals, even though nanostructuring leads to less favorable optical properties of Co3O4. The stability of the used Ru(bpy)32+ sensitizer, which is a function of mode of irradiation (wavelength) and buffer capacity, was found to be a major factor in controlling the evolved oxygen quantity.